QUALITATIVE ANALYSIS OF DRUG SUBSTANCES IN RHEUMATIC JAMU SAMPLES USING THIN LAYER CHROMATOGRAPHY - Resma Dwi Putri Fitrianasari; Perdana Priya Haresmita; Herma Fanani Agusta (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Since ancient times, jamu have been used to treat various diseases. Recently, the number of jamu has increasing and this has led several manufacturers to commit fraud. They added drug substances (DS) into jamu for gaining the effect of jamu so that can raise the sales of jamu in market . The addition of DS into herbal medicine is a violation of the regulation issued by The Ministry of Health. Such practices can cause side effects that are very dangerous for health. The purpose of this research is to analyze the presence of DS in jamu samples that are frequently consumed and circulated in Kranggan, Temanggung and Magelang city. Thin-Layer Chromatography (TLC) was employed to detect the presence of prednisone, paracetamol, and mefenamic acid. The working principle of the separation of compounds with TLC is to separate samples based on the partition difference between samples and the solvent used. In this case, the stationary phase used is the silica gel plate GF254 with the mobile phase for prednisone using ethyl acetate:chloroform (4:1), mefenamic acid using chloroform:methanol (9:1),and paracetamol using chloroform:ethanol (8:1). As a result of qualitative analysis, jamu samples in those areas do not contain any drug substances that were suspected to be present. Keywords: jamu, prednisone, paracetamol, mefenamic acid